Outpatient Register of Patients with Acute Myocardial Infarction: Assessment of the Hypertension Impact on Long-term Prognosis - D. P. Sichinava; E. P. Kalaydzhyan; N. P. Kutishenko; S. Yu. Martsevich (Столичная издательская компания, 2019)
Aim. To assess the impact of arterial hypertension (AH) on the long-term outcomes in patients after acute myocardial infarction (AMI).Material and methods. 160 patients were included: 106 (66.2%) men and 54 (33.8%) women, average age 74.2±11.2 years, discharged from Moscow hospitals with a diagnosis of AMI (from March 01, 2014 till June 30, 2015) and applied to the city polyclinic №9 in Moscow or its branches for outpatient observation. The information was obtained on the basis of medical documentation of the polyclinic and data of patients' examination/questioning by phone, conducted every 2 months. The follow-up duration was 1 year, the incidence of cardiovascular complications (CVC) was estimated: death, nonfatal AMI, nonfatal cerebral stroke, new cases of atrial fibrillation (AF), hospitalization for unstable angina, hypertensive crisis, heart failure, unplanned surgical interventions on the heart and blood vessels.Results. AH before the development of reference AMI was observed in 118 (73.4%) patients: 48 women and 70 men; in women, AH was recorded more often than in men: 88.9% and 66.0%, respectively, p<0.05. Patients with AH were older than patients without AH: 63.0 (54.0; 74.0) and 55.5 (49.0; 61.0) years, respectively, p<0.001, among them there were more retirees 76 (64.4%) and patients with disabilities 45 (38.1%), p<0.05. Patients with AH compared with patients without AH were less likely to smoke (18.6% and 38.1%, respectively) and drank alcohol (30.5% and 52.4%, respectively), p<0.05 for both; more likely to visit the outpatient clinic (89.0% and 66.7%, respectively), p<0.05. There were no significant differences between the groups of patients with and without AH in the history of cerebral stroke, AMI, arrhythmia by AF type, diabetes mellitus and obesity, except for angina of tension (18.6% and 2.4%, respectively) and hypercholesterolemia (37.3% and 11.9%, respectively), p<0.05 for both. Despite the fact that patients with AH were significantly more often prescribed antihypertensive, lipid-lowering and antithrombotic drugs before reference AMI, the frequency of their use was low: renin-angiotensin-aldosterone system blockers were prescribed in 70 (59.3%) patients, beta-blockers - in 35 (29.7%), calcium antagonists - in 20 (16.9%), diuretics - in 13(11.0%), antiplatelet agents - in 39 (33.1%), statins - in 9 (7.6%) patients. After one year of follow-up, CVC was registered in 33 (28.0%) patients with AH and 9 (21.4%) patients without AH (p=0.41). There was no statistically significant effect of AH on long-term outcomes of AMI, adjusted risk ratio =1.30 [95% confidence interval 0.68- 2.49], p>0.05. The effect of AH on the development of CVC, estimated using the Kaplan-Mayer curve, was not statistically significant (p=0.120).Conclusion. During 1 year of follow-up after AMI in patients with AH the frequency of CVC - death, nonfatal AMI, nonfatal cerebral stroke, new cases of AF, hospitalization for unstable angina, hypertensive crisis, heart failure - did not exceed the overall frequency of CVC in patients without AH.